PETROLOGY OF A LOWER CRUSTAL XENOLITH SUITE FROM DIKES AND EXPLOSION PIPES OF THE KANDALAKSHA GRABEN - Koreshkova M.Yu.; Ivanikov V.V.; Levskii L.K. (My University, 2001)
The lower crustal xenolith suite contained in alkaline-ultramafic dikes and the explosion pipes of the Kandalaksha graben, northwestern Belomorie, consists of Grt granulites (Grt-Cpx-Pl ± Qtz), two-feldspar Grt granulites (Grt-Cpx-Pl-K-Fsp ± Qtz), two-pyroxene Grt granulites (Grt-Cpx-Opx-Pl ± Qtz), Grt two-pyroxene rocks (Grt-Cpx-Opx ± Qtz), and Grt clinopyroxene rocks (Grt-Cpx ± Qtz). Based on their chemistry, the rocks are classified into four groups. The most abundant varieties correspond to tholeiitic basalt, which is similar to Archean tholeiite (TH2; Condie, 1983), and andesite, which is probably related to the tholeiitic basalts. Rocks of picrobasaltic composition, varieties affiliating with the gabbro-anorthosite association, and olivine gabbroids of troctolitic composition are more rare. The textures of the rocks and the systematic variations in the mineral chemistry of some xenoliths of the Grt two-pyroxene rocks and Grt granulites suggest that the garnet crystallized after plagioclase as a product of chemical reactions at a temperature decrease. The geotherm derived from the calculated T-P parameters of Grt granulite xenoliths corresponds to a cooling stage, which proceeded after high-temperature metamorphic reactions and before the transportation of the xenoliths to the surface. The apparent age of the Cpx-Grt mineral pair from a Grt granulite xenolith is 1.36 Ga by the Rb-Sr system and 1.33 Ga by the Sm-Nd system and corresponds to the time when the rock temperature decreased to approximately 600-650°C. The age of the high-temperature metamorphism is older than 1.7 Ga, as follows from the U-Pb zircon age of a two-feldspar Grt granulite xenolith (Vetrin and Nemchin, 1998). The value of 1.7 Ga is only insignificantly different from the estimated age of Svecofennian events in the eastern Baltic Shield, and, hence, events in the upper and lower parts of the regional Precambrian crust could be interrelated. However, the xenoliths show a shift in their age toward younger values. The age of their protolith can be assayed by the TDM model age of xenoliths of a Grt granulite and a Grt two-pyroxene rock (2.81 and 2.96 Ga, respectively).
Keywords: Archean; Precambrian; Докембрий::Архей; Precambrian; Precambrian::Archean; Докембрий